Biocomputing 2012 2011
DOI: 10.1142/9789814366496_0016
|View full text |Cite
|
Sign up to set email alerts
|

Functional Annotation of Intrinsically Disordered Domains by Their Amino Acid Content Using Idd Navigator

Abstract: Function prediction of intrinsically disordered domains (IDDs) using sequence similarity methods is limited by their high mutability and prevalence of low complexity regions. We describe a novel method for identifying similar IDDs by a similarity metric based on amino acid composition and identify significantly overrepresented Gene Ontology (GO) and Pfam domain annotations within highly similar IDDs. Applications and extensions of the proposed method are discussed, in particular with respect to protein functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…We have previously shown that amino acid content similarity, instead of sequence similarity, can be used to predict a function associated with an IDR. 13 While the method works better than random, the results here suggest several avenues for improvement, such as location preference. Indeed, location of IDRs has been previously used in the function prediction of proteins with long disordered regions.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…We have previously shown that amino acid content similarity, instead of sequence similarity, can be used to predict a function associated with an IDR. 13 While the method works better than random, the results here suggest several avenues for improvement, such as location preference. Indeed, location of IDRs has been previously used in the function prediction of proteins with long disordered regions.…”
Section: Discussionmentioning
confidence: 79%
“…12 Indeed, the use of amino acid content similarity alone can help identify IDRs with similar functions at statistically significant levels. 13 Thus, the amino acid content and the resultant overall chemical composition of the IDR are clearly important. For instance, it has been observed that the amino acid composition, specifically the fraction of Gly residues, is similar in the N-terminal domains of core histones H2A and H4 in spite of poor sequence similarity.…”
Section: Introductionmentioning
confidence: 99%
“…Protein disorder was predicted using the IUPRED algorithm (Dosztányi et al, 2005a(Dosztányi et al, , 2005b. The aa composition of the C-terminal IDD of FXR1 was determined using IDD Navigator with IUPRED disordered domain prediction (Patil et al, 2012) along with the ProtParam tool (https://web.expasy.org/protparam/); Wilkins et al, 1999). For phosphorylation prediction, the sequences of the His-GB1-FXR1 A/E, or FMR1 (uniprot) were analyzed using the NETphos 3.1 predictor (serine phosphorylation) and IUPRED (disorder).…”
Section: Softwarementioning
confidence: 99%
“… 42 However, unlike the latter, they possess a disordered C-terminal region, a feature that they share with CLOCK and BMAL1 (where it serves the regulation of their activity) 9 , 43 45 as well as PER (where it contains binding sites for kinases and CRY). 46 , 47 The presence of such intrinsically disordered domains (IDDs) 48 is not just a shared property among mammalian clock proteins and other components involved in transcriptional regulation; 49 disordered C-terminal regions also figure prominently in the proteins that assemble the cyanobacterial KaiABC PTO. 17 , 50 A structural and functional understanding of these regions, e.g., the C-terminal tail of KaiB that is important for proper rhythmicity of the cyanobacterial timer, 51 has remained elusive thus far, despite the use of a hybrid structural biology approach to dissect the KaiABC clock.…”
Section: Clock Architecturementioning
confidence: 99%
“…Cryptochromes do not share architectural features with CLOCK, BMAL1, and PER proteins because they lack PAS domains but instead contain the PHR that is structurally similar to photolyase . However, unlike the latter, they possess a disordered C-terminal region, a feature that they share with CLOCK and BMAL1 (where it serves the regulation of their activity) , as well as PER (where it contains binding sites for kinases and CRY). , The presence of such intrinsically disordered domains (IDDs) is not just a shared property among mammalian clock proteins and other components involved in transcriptional regulation; disordered C-terminal regions also figure prominently in the proteins that assemble the cyanobacterial KaiABC PTO. , A structural and functional understanding of these regions, e.g., the C-terminal tail of KaiB that is important for proper rhythmicity of the cyanobacterial timer, has remained elusive thus far, despite the use of a hybrid structural biology approach to dissect the KaiABC clock . The challenges posed by this “simple clock”, regardless of the application of a battery of structural and molecular biology as well as genetic tools, may offer a lesson for the path ahead in structural studies directed at the cogs and gears of the arguably more complex mammalian clock (DOI: 10.1021/bi500731f).…”
Section: Clock Architecturementioning
confidence: 99%